Planul-cadru de învățământ ca obiect al manifestării curriculare [Articol] - Guțu, Vladimir; Bragarenco, Nicolae; Toma, Natalia (CEP USM, 2024)
The development and monitoring of the functioning of the framework plan for primary, secondary and high school education is a current issue and falls within the strategy of updating the National Curriculum. The article is built according to the following logic: (•) defining and characterizing the Education Framework Plan as a curricular product; (•) comparative analysis of the Framework Plan from the Republic of Moldova with the Education Plans from different countries; (•) establishing the place of key competencies in the structure of the National Curriculum; (•) establishing strong relationships of school subjects in relation to key competencies; (•) presentation of the logic of capitalizing on key skills and the guidelines for the development of the Education Framework Plan.
THE EDUCATIONAL FRAMEWORK PLAN AS THE OBJECT OF THE CURRICULUM MANIFESTATION
Keywords: curriculum development; curriculum monitoring; Education key skills; National Curriculum; Plan-cadru